Comparative study between XFEM and Hashin damage criterion applied to failure of composites. (June 2017) - Duarte, A.P.C.; Díaz Sáez, A.; Silvestre, N.
Abstract: This paper presents a comparative study between Hashin damage criterion and the eXtended Finite Element Method (XFEM) applied to the failure of fiber reinforced polymers (FRP). A brief literature review on failure criteria to predict the failure of FRP is firstly presented. Then, finite element models of square plates with different layer configurations, containing a circular hole with distinct radii and subjected to monotonic uniaxial tension are described within the framework of ABAQUS package. The models are validated by comparison between the numerical results and those of a benchmark model. Finally, the influence of (i) stacking sequence, (ii) hole radii and (iii) failure criteria (Hashin and XFEM) on the load vs. elongation paths, stresses distributions and collapse configurations of the plates is shown and discussed and some conclusions are drawn. Graphical abstract: Highlights: Fiber reinforced polymer (FRP) plates with circular hole are numerically studied. Comparative study between Hashin criterion and XFEM on failure of FRP plates is made. Until first ply failure, both approaches (Hashin and XFEM) provide similar results. Hashin-based models present maximum loads 20% lower than XFEM-based models. In Hashin-based models, shear resistance in fiber breakage mode plays a key role.